Assessment of the impact of budget decentralization on sustainable development of territorial communities in Ukraine - Muzychenko, Ganna; Koliada, Tetiana; Xin, Ding (<center>Conference Proceedings Determinants Of Regional Development</center>, 2021)
Peculiarities of territorial community (hromada) development management are revealed and theoretical approaches to budget decentralization in Ukraine are substantiated. Based on the analysis of the composition and structure of local budget revenues, as well as the calculation of indicators of financial independence of territorial communities (hromadas), it is proved that the modern budget system of Ukraine is characterized by a high degree of centralization of budget resources, which does not provide real independence. To build an effective and efficient model of budget decentralization is to determine the tax potential of a separate administrative-territorial unit (territorial community). For further success of decentralization, it is necessary to determine the optimal scope of state functions, which are expedient and cost-effective to delegate to the appropriate local level on a permanent basis, thus translating them into their own functions of local governments.